A video distribution game with enhanced quality of experience for wireless networks. Issue 3 (1st September 2013) - Goudarzi, Pejman
Abstract : Video communication over unpredictable wireless medium is a challenging research area. Many mathematical solutions have been proposed by researchers for high‐quality video forwarding over such networks. An important example is the game theory. The non‐cooperative game theory can be adopted to represent the selfish behaviour of network users. In the current study, a non‐cooperative quality game framework (QGF) has been introduced, in which by exploiting a related quality metric, scalable video users try to enhance their perceived quality in a distributed manner in mobile ad‐hoc networks. The behaviour of the Nash equilibrium point has been analysed and a distributed resource allocation strategy has been introduced. Also, the quality properties of the proposed QGF under the user churn effects have been investigated. The assigned rates in the quality game can be considered as rate‐feedbacks for on‐line rate adaptation of a moderate scalable video encoder such as HEVC, H.264/MPEG4 AVC etc. Some experimental results have been presented to validate the theoretical results.